FOREIGN INVESTMENT IS AN IMPORTANT STAGE OF ECONOMIC GROWTH - Khasan Akhmedov; Abdurasulov Humoyun (Innovate Conferences, 2025)
The article reflects that foreign investment is an important source of economic growth, and that subjects and objects of investment are equally interested in them.
Keywords: foreign investment, economic growth, capital, securities, investment attractiveness, investment environment.